The usefulness of mobile applications in shaping responsible consumption - Jaska Ewa; Werenowska Agnieszka; Balińska Agata (International Journal of Management and Economics, 2025)
The main purpose of the article is to present a catalog of features of a useful mobile application in the context of responsible consumption. To recognize the usefulness of the application, examples of eco-applications were used, and representatives of the Z generation were asked about the features of the optimal application reasons for using them, and for whether they are worth recommending. The article uses the analysis of domestic and foreign literature, as well as the results of own research carried out in the first quarter of 2023, in which 747 respondents participated. The hypotheses confirmed that the most important feature of a useful application from a functionality perspective is the lack of fees for its use; from a technical solutions perspective, speed of operation, and from a security perspective, payment protection. The hypothesis that more promoters of pro-environmental mobile applications are in the group of women was also positively verified.